2020
DOI: 10.3389/fneur.2020.00939
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis Coexisting With Primary Sjögren's Syndrome: Report of Three Cases and Literature Review

Abstract: Objective: The coexistence of myasthenia gravis (MG) and primary Sjögren's syndrome (pSS) is rarely reported. This study aims to describe the clinical features, treatment and outcome of MG coexisting with pSS. Materials and Methods: Herein we reported three cases with the two coexisting diseases, and also searched the PubMed, Medline databases, and China Wanfang databases for the relevant case reports written in English, Chinese, or Japanese with detailed data. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The relationship between MG and other ADs is also still controversial to date. Similar to the findings observed in patients with SLE, MG combined with AITD or RA tended to be a milder form of the disease, [3,26] and comorbidity with MG did not seem to adversely affect the course of SS [32]. However, some studies showed that patients with both MG and HT had a more severe MG status and that MG in association with other autoimmune disorders had a less favorable prognosis [35,62].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The relationship between MG and other ADs is also still controversial to date. Similar to the findings observed in patients with SLE, MG combined with AITD or RA tended to be a milder form of the disease, [3,26] and comorbidity with MG did not seem to adversely affect the course of SS [32]. However, some studies showed that patients with both MG and HT had a more severe MG status and that MG in association with other autoimmune disorders had a less favorable prognosis [35,62].…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, patients with MG and SLE were previously shown to predominantly have generalized MG [31]. Most MG patients coexisting with primary Sjögren syndrome were classified as generalized MG, [32] while thyroid diseases showed the highest association rate with ocular early-onset MG [33]. 6 Acta Neurologica Scandinavica Thymoma, a rare tumor of the thymus, was found to be associated with many ADs including MG, pure red cell aplasia, and SLE [34].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the association between SS and MG, mainly in the early stage, has been reported. MG was reported before the diagnosis of SS, with initial bulbar symptoms of MG and predominantly positive anti-Ro/SSA antibodies, as in the case presented, and the presence of constitutional symptoms should be considered significant, as it may be associated with thymoma and mediastinal tumor masses [8][9][10]. In this case, there was no thymoma or mediastinal mass.…”
Section: Discussionmentioning
confidence: 66%
“…SS is a B-cell mediated autoimmune disease with anti-SSA (Ro), anti-SSB, and ANA Abs. The frequency of neurological involvement, such as peripheral neuropathy, aseptic meningitis, NMO, and MS in SS is up to 20% ( 98 100 ). However, the coexistence of MG and SS has rarely been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al. reviewed 17 patients with both diseases and revealed that MG may develop before or after SS ( 100 ). The coexistence of both diseases predominantly affected female and EOMG patients.…”
Section: Resultsmentioning
confidence: 99%